Two-Dimensional Legendre Wavelets for Solving Time-Fractional Telegraph Equation (Advances in Applied Mathematics and Mechanics, 2014)
In this paper, we develop an accurate and efficient Legendre wavelets method for numerical solution of the well known time-fractional telegraph equation. In the proposed method we have employed both of the operational matrices of fractional integration and differentiation to get numerical solution of the time-telegraph equation. The power of this manageable method is confirmed. Moreover, the use of Legendre wavelet is found to be accurate, simple and fast.